GEOLOGICAL AND ENGINEERING SURVEYS FOR WORKING PROJECT OF OBJECT BUILDING INTENDED FOR RECREATION PURPOSES IN CHERNIGOV (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of geological and engineering surveys that were carried out on the area of prospective object building intended for recreation purposes on the peninsula between the Stryzhen River and the Desna River in the city of Chernihiv are set up in the article. Categories of difficulty concerning geotechnical conditions are substantiated. Keywords:surveys, section, geotechnical element, groundwater.